2015
DOI: 10.1155/2015/203679
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of Total Phenol, Flavonoid Contents, and Antioxidant Potential of FolkloricLannea coromandelicaUsingIn VitroandIn VivoAssays

Abstract: The aim of this study was to determine the impending antioxidant properties of different extracts of crude methanolic extract (CME) of leaves of Lannea coromandelica (L. coromandelica) and its two ethyl acetate (EAF) and aqueous (AqF) subfractions by employing various established in vitro systems and estimation of total phenolic and flavonoid content. The results showed that extract and fractions possessed strong antioxidant activity in vitro and among them, EAF had the strongest antioxidant activity. EAF was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 62 publications
3
20
0
1
Order By: Relevance
“…Chromatographic techniques include gas chromatography (GC), gas chromatography-mass spectrometry (GC-MS), high-pressure liquid chromatography (HPLC), and liquid chromatography-mass spectrometry (LC-MS) [14]. Various spectroscopic techniques used to determine TPC are Fourier Transform Infrared (FT-IR) spectroscopy, Raman spectroscopy, and Folin-Ciocalteu (F-C) assay using UV-VIS spectroscopy [15] [16]. TPC is also indirectly measured in terms of antioxidant activity (AOA) of an extract as results have shown that there is a direct correlation of AOA and TPC content [17].…”
Section: Introductionmentioning
confidence: 99%
“…Chromatographic techniques include gas chromatography (GC), gas chromatography-mass spectrometry (GC-MS), high-pressure liquid chromatography (HPLC), and liquid chromatography-mass spectrometry (LC-MS) [14]. Various spectroscopic techniques used to determine TPC are Fourier Transform Infrared (FT-IR) spectroscopy, Raman spectroscopy, and Folin-Ciocalteu (F-C) assay using UV-VIS spectroscopy [15] [16]. TPC is also indirectly measured in terms of antioxidant activity (AOA) of an extract as results have shown that there is a direct correlation of AOA and TPC content [17].…”
Section: Introductionmentioning
confidence: 99%
“…The absorbance for extract was 1.003 and 1.593 for the standard. From the results obtained in this study, it is suggested that the ethanolic extract potentially donates the electron to reactive free radicals to convert them into more stable nonreactive form and terminates the free radical chain reaction [34].…”
Section: Biswas and Senmentioning
confidence: 78%
“…It was found that the TPs significantly decreased hydroxyl radical concentration in a dose-dependent manner at the test concentrations. Superoxide radicals cause oxidative damage to many biomolecules and are the most common free radicals produced in vivo by several oxidative enzymes [23] . The ability of the TPs to scavenge superoxide radicals was determined by the reduction of NBT.…”
Section: Resultsmentioning
confidence: 99%